Method for preparing emulsion gel from shellac nanoparticle-cationic starch compound
Through high-speed shear homogenization treatment of shellac nanoparticles-cationic starch composite and soybean oil, the problems of complex and poor stability of emulsion gel preparation process in the prior art are solved, and the high stability and rheological characteristics of emulsion gel are improved, which is suitable for the food industry.
Patent Information
- Application Number
- CN202411796504.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-04-08
AI Technical Summary
The process of the prior art is complicated and cumbersome when preparing emulsion gels. Using shellac nanoparticles and cationic starch alone as emulsifiers cannot form a stable gel structure, which limits its performance under harsh application conditions.
The shellac nanoparticle-cationic starch complex was used to prepare the shellac nanoparticle solution and the cationic starch solution, and then mix it and undergo high-speed shear homogenization treatment with soybean oil to prepare an emulsion gel.
It has achieved the improvement of the stability and rheological characteristics of the emulsion gel, has excellent storage stability and edibleness, is suitable for the food industry, and has expanded the application scope of shellac.
Smart Images

Figure CN119775594A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of emulsion gel preparation, in particular to a method for preparing emulsion gel by utilizing shellac nanoparticle-cationic starch complex. Background Art
[0002] Shellac is a natural biopolymer with film-forming, water-resistant and biocompatible properties. Through nano-processing, shellac nanoparticles show excellent emulsification ability and antioxidant properties, and have a wider range of applications in emulsion and gel systems.
[0003] Cationic starch, as a modified natural polysaccharide, has outstanding performance in emulsion stability and gel network formation due to its positive charge characteristics, and has good biodegradability, which is in line with the green environmental protection trend.
[0004] As a functional material, emulsion gel is widely used in food, cosmetics and drug delivery. It has the dual characteristics of emulsion and gel, can encapsulate and protect active ingredients, and provide good stability and controlled release performance. However, traditional emulsifiers are mostly synthetic chemicals, which pose environmental pollution and health risks. Therefore, finding natural, environmentally friendly and efficient emulsifiers has become a research hotspot.
[0005] However, in actual use of the existing technology, commonly used methods include adding a cross-linking agent to the aqueous phase or first preparing an emulsion and then performing secondary gelation, but these processes are usually complicated and cumbersome. In addition, the emulsion prepared using shellac nanoparticles and cationic starch alone as emulsifiers is still unstable and cannot form a gel structure, which limits its performance under harsh application conditions. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing an emulsion gel using a shellac nanoparticle-cationic starch complex, so as to solve the problem that the process is relatively complicated and cumbersome, and the emulsion prepared using shellac nanoparticles and cationic starch alone as emulsifiers cannot form a gel structure, thereby limiting its performance under harsh application conditions.
[0007] To achieve the above object, the present invention provides the following technical solution: a method for preparing an emulsion gel using a shellac nanoparticle-cationic starch complex, comprising the following steps:
[0008] S1. Material preparation: prepare shellac, starch, 3-chloro-2-hydroxypropyl-trimethylammonium chloride solution, distilled water and soybean oil, wherein the starch includes but is not limited to tapioca starch, corn starch and potato starch;
[0009] S2. preparing a shellac nanoparticle solution A: dissolving shellac in anhydrous ethanol, and then quickly injecting the anhydrous ethanol solution containing shellac into distilled water with a syringe to obtain a shellac nanoparticle solution, and then performing rotary evaporation to obtain a shellac nanoparticle solution A;
[0010] S3, preparing cationic starch solution B: dissolving starch in isopropanol, and stirring at room temperature, then adding sodium hydroxide solution dropwise, while continuing to stir, then adding 3-chloro-2-hydroxypropyl-trimethylammonium chloride solution and stirring in a water bath to react, after the reaction is completed, using an acid to adjust the pH value to 6.2, adding anhydrous ethanol and filtering to obtain a precipitated sample, then rinsing the sample several times and filtering again and finally drying to obtain cationic starch, dissolving the cationic starch in distilled water, heating in a water bath and magnetically stirring, and finally obtaining cationic starch solution B;
[0011] S4, preparing a mixed solution C: adding the shellac nanoparticle solution A obtained in step S2 to the cationic starch solution B in step S3 to obtain a shellac nanoparticle-cationic starch mixed solution C;
[0012] S5, preparing an emulsion gel: adding soybean oil to the mixed solution C obtained in step S4, and subjecting the mixed solution C with the soybean oil to high-speed shear homogenization treatment to obtain an emulsion gel.
[0013] Preferably, the temperature in the rotary evaporation of step S2 is 40° C. and the rotation speed is 100 r / min. The concentrations of the shellac nanoparticle solution A in step S2 and the cationic starch solution B in step S3 are respectively 0.5% to 1.0% (w / v).
[0014] Preferably, in step S3, 3-chloro-2-hydroxypropyl-trimethylammonium chloride solution is added to carry out stirring reaction in a water bath, the water bath heating temperature is 70° C. to 90° C., the heating time is 10 to 40 min, and the acid agent in step S3 is 0.1 M hydrochloric acid solution.
[0015] Preferably, the stirring rate of the magnetic stirring in step S3 is 300-500 rpm, and the steps of rinsing the sample multiple times, filtering again and finally drying in step S3 are as follows: rinsing the sample 3-5 times with anhydrous ethanol, filtering, and then drying in an oven.
[0016] Preferably, the high-speed shear rate of the homogenizer in step S5 is 9000-15000 r / min for 2-4 min, and the volume ratio of the shellac nanoparticle solution A to the cationic starch solution B in step S4 includes but is not limited to 5:1, 4:1, 2:1 and 1:2.
[0017] Preferably, the volume ratio of the mixed solution C to the soybean oil in step S5 includes but is not limited to 4:1, 7:3, 3:2, 5:5, 2:3, 3:7 and 1:4.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] 1. The present invention uses shellac as a raw material and provides a method for preparing an emulsion gel, which has the characteristics of biodegradability, biocompatibility, pH responsiveness and FDA-approved safety, and expands the application range of shellac, wherein shellac nanoparticles and cationic starch are compounded through hydrogen bonds and ionic bonds, and the prepared emulsion gel has excellent storage stability and rheological properties, and is edible. The preparation method is novel and simple, easy to realize industrial production, and suitable for the food industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 Schematic diagram of droplet diameter of the composite stabilized emulsion prepared in Comparative Example 1, Comparative Example 2 and Example 1 of the present invention;
[0021] Figure 2 Schematic diagram of the storage modulus (G') and loss modulus (G") of the emulsions in Comparative Example 1, Comparative Example 2 and Example 1 of the present invention;
[0022] Figure 3 Schematic diagram of the apparent viscosity of the emulsions in Comparative Example 1, Comparative Example 2 and Example 1 of the present invention. DETAILED DESCRIPTION
[0023] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] The test methods for the properties of the composite and the physicochemical properties of the emulsion gel in the embodiments of the present invention are as follows:
[0025] Droplet size determination method: The droplet size of the emulsion was determined by a laser particle size analyzer (Mastersizer 3000, Malvern Instruments Ltd., UK). The refractive index of soybean oil and dispersant was set to 1.46 and 1.33, respectively. The samples were diluted to 1% (w / v) concentration with distilled water at the corresponding pH value and measured immediately after preparation. The droplet size measurement was calculated as the average volume diameter value (D 4,3 ).
[0026] Rheological properties: The rheological properties of the emulsions were measured by a rheometer (Kinexus Pro+, Malvern Instruments Ltd., UK) with a plate diameter of 20 mm and a gap height of 1 mm. The storage modulus (G') and loss modulus (G") were measured at 25 °C with a frequency sweep range of 0.1 to 100 rad / s and a constant strain of 0.5%. In addition, the apparent viscosity was measured with a shear rate range of 0.1 to 100 s -1 .
[0027] Embodiment 1
[0028] See also Figure 1-3 The present invention provides a technical solution: a method for preparing an emulsion gel using a shellac nanoparticle-cationic starch complex, comprising the following steps:
[0029] S1. Material preparation: prepare shellac, tapioca starch, 3-chloro-2-hydroxypropyl-trimethylammonium chloride (HAC) solution, distilled water and soybean oil;
[0030] S2. Prepare shellac nanoparticle solution A: weigh 1 g of shellac and dissolve it in 60 mL of anhydrous ethanol. Use a syringe to quickly inject the anhydrous ethanol solution containing shellac into 140 mL of distilled water to obtain a shellac nanoparticle solution. Subsequently, rotary evaporate to 100 mL at 40°C and 100 r / min to obtain a shellac nanoparticle solution A with a concentration of 1% (w / v).
[0031] S3. Preparation of cationic starch solution B: 5 g of cassava starch was dissolved in 500 mL of isopropanol, stirred at room temperature for 15 min, 25 mL of 2M NaOH solution was added dropwise, stirred for 60 min, 17 mL of HAC solution was added, and the mixture was stirred in a 60°C water bath for 5 h. After the reaction, the pH was adjusted to 6.2 with 0.1 M hydrochloric acid solution, 250 mL of anhydrous ethanol was added, and the precipitated sample was obtained by filtration. The sample was rinsed with anhydrous ethanol for 3 to 5 times and then filtered. Finally, the sample was placed in a 40°C oven for drying to obtain cationic starch, i.e., HAC-modified cassava starch. 0.25 g of HAC-modified cassava starch was dissolved in 25 mL of distilled water, placed in a 90°C water bath, and reacted with a magnetic stirring at 300 rpm for 30 min to obtain a 1% (w / v) cationic starch solution B.
[0032] S4, preparing a mixed solution C: adding the shellac nanoparticle solution A obtained in step S2 to the cationic starch solution B in step S3, wherein the volume ratio of the shellac nanoparticle solution A to the cationic starch solution B is 4:1, to obtain a shellac nanoparticle-cationic starch mixed solution C;
[0033] S5. Obtaining an emulsion gel: adding soybean oil to the mixed solution C in step S4, wherein the volume ratio of the mixed solution C to the soybean oil is 3:7, and subjecting the mixed solution C to which the soybean oil is added to high-speed shear homogenization with a homogenizer to obtain an emulsion gel, wherein the shear rate is 13000 r / min and the time is 3 min.
[0034] The particle size test results of the emulsion gel prepared in Example 1 show that the droplet size of the emulsion gel prepared using the shellac nanoparticle-cationic starch composite of this example is 60 μm, and the particle size distribution is uniform. The emulsion has high stability, especially after being stored for 42 days, it still maintains a gel state.
[0035] Embodiment 2
[0036] The difference from the first embodiment is that:
[0037] S4. Prepare mixed solution C: the volume ratio of shellac nanoparticle solution A to cationic starch solution B is 2:1.
[0038] The particle size test results of the emulsion gel prepared in Example 2 show that the droplet size of the emulsion gel prepared using the shellac nanoparticle-cationic starch composite of this example is 99 μm, and the particle size distribution is uniform. The emulsion stability is slightly higher and the gel properties are maintained after 42 days of storage.
[0039] Embodiment 3
[0040] The difference from the first embodiment is that:
[0041] S4. Prepare a mixed solution C: the volume ratio of shellac nanoparticle solution A to cationic starch solution B is 1:2.
[0042] S5. Prepare an emulsion gel: the volume ratio of shellac nanoparticle-cationic starch mixed solution C to soybean oil is 2:8.
[0043] The particle size test results of the emulsion gel prepared in Example 3 show that the droplet size of the emulsion gel prepared using the shellac nanoparticle-cationic starch composite of this example is 129 μm, and the particle size distribution is uniform, the emulsion stability is poor, the amount of the composite is insufficient to cover the oil-water interface, and stratification occurs after storage for 42 days.
[0044] Embodiment 4
[0045] The difference from the first embodiment is that:
[0046] The following steps are involved:
[0047] S1. Material preparation: prepare shellac, corn starch, HAC solution, distilled water and soybean oil;
[0048] S2. Preparation of shellac nanoparticle solution A: 0.5 g of shellac was dissolved in 60 mL of anhydrous ethanol, and the anhydrous ethanol solution containing shellac was quickly injected into 140 mL of distilled water with a syringe to obtain a shellac nanoparticle solution. Subsequently, the solution was rotary evaporated to 100 mL at 40° C. and 100 rpm to obtain a shellac nanoparticle solution A with a concentration of 0.5% (w / v).
[0049] S3. Preparation of cationic starch solution B: 5 g corn starch was dissolved in 500 mL isopropanol, stirred at room temperature for 15 min, 25 mL 2 M NaOH solution was added dropwise, stirred for 60 min, 10 mL HAC solution was added, and the mixture was stirred in a 60°C water bath for 5 h. After the reaction, the pH was adjusted to 6.2 with 0.1 M hydrochloric acid solution, 250 mL anhydrous ethanol was added, and the precipitated sample was obtained by filtration. The sample was rinsed with anhydrous ethanol for 3 to 5 times and then filtered. Finally, the sample was placed in a 40°C oven for drying to obtain cationic starch, i.e., HAC-modified corn starch. 0.25 g HAC-modified corn starch was dissolved in 25 mL distilled water, placed in a 70°C water bath, and reacted with a magnetic stirring at 300 rpm for 40 min to obtain a 1% (w / v) cationic starch solution B.
[0050] S4, preparing a mixed solution C: adding the shellac nanoparticle solution A obtained in step S2 to the cationic starch solution B in step S3, wherein the volume ratio of the shellac nanoparticle solution A to the cationic starch solution B is 5:1, to obtain a shellac nanoparticle-cationic starch mixed solution C;
[0051] S5. Obtaining an emulsion gel: adding soybean oil to the mixed solution C in step S4, wherein the volume ratio of the mixed solution C to the soybean oil is 8:2, and subjecting the mixed solution C to which the soybean oil is added to high-speed shear homogenization by a homogenizer to obtain an emulsion gel, wherein the shear rate is 9000 r / min and the time is 2 min.
[0052] The particle size test results of the emulsion prepared in Example 4 show that the droplet size of the emulsion prepared using the shellac nanoparticle-cationic starch complex of this example is 308 μm, and the particle size distribution is uniform, but the emulsion cannot form a gel.
[0053] Embodiment 5
[0054] The difference from the first embodiment is that:
[0055] The following steps are involved:
[0056] S1. Material preparation: prepare shellac, potato starch, HAC solution, distilled water and soybean oil;
[0057] S2. Prepare shellac nanoparticle solution A: weigh 1 g of shellac and dissolve it in 60 mL of anhydrous ethanol. Use a syringe to quickly inject the anhydrous ethanol solution containing shellac into 140 mL of distilled water to obtain a shellac nanoparticle solution. Subsequently, rotary evaporate to 100 mL at 40°C and 100 r / min to obtain a shellac nanoparticle solution A with a concentration of 1% (w / v).
[0058] S3. Preparation of cationic starch solution B: 5 g of potato starch was dissolved in 500 mL of isopropanol, stirred at room temperature for 15 min, 25 mL of 2M NaOH solution was added dropwise, stirred for 60 min, 20 mL of HAC solution was added, and the mixture was stirred in a 60°C water bath for 5 h. After the reaction, the pH was adjusted to 6.2 with 0.1 M hydrochloric acid solution, 250 mL of anhydrous ethanol was added, and the precipitated sample was filtered out by suction. The sample was rinsed with anhydrous ethanol for 3 to 5 times and then filtered out by suction. Finally, the sample was placed in a 40°C oven for drying to obtain cationic starch, i.e., HAC-modified potato starch. 0.25 g of HAC-modified potato starch was dissolved in 25 mL of water, placed in a 90°C water bath, and reacted with magnetic stirring at 500 rpm for 10 min to obtain 1% (w / v) cationic starch solution B.
[0059] S4, preparing a mixed solution C: adding the shellac nanoparticle solution A obtained in step S2 to the cationic starch solution B in step S3, wherein the volume ratio of the shellac nanoparticle solution A to the cationic starch solution B is 5:1, to obtain a shellac nanoparticle-cationic starch mixed solution C;
[0060] S5. Obtaining an emulsion gel: adding soybean oil to the mixed solution C in step S4, wherein the volume ratio of the mixed solution C to the soybean oil is 3:7, and subjecting the mixed solution C to which the soybean oil is added to high-speed shear homogenization with a homogenizer to obtain an emulsion gel, wherein the shear rate is 15000 r / min and the time is 4 min.
[0061] The particle size test results of the emulsion gel prepared in Example 5 show that the droplet size of the emulsion gel prepared by using the shellac nanoparticle-cationic starch composite of this example is 191 μm, and the particle size distribution is uniform, and the emulsion has high stability.
[0062] Embodiment 6
[0063] The difference from the fifth embodiment is that:
[0064] S5. Obtaining an emulsion gel: adding soybean oil to the mixed solution C in step S4, wherein the volume ratio of the mixed solution C to the soybean oil is 2:8, and subjecting the mixed solution C to which the soybean oil is added to high-speed shear homogenization with a homogenizer to obtain an emulsion gel, wherein the shear rate is 15000 r / min and the time is 4 min.
[0065] The test results of the particle size of the emulsion gel prepared in Example 6 show that the average particle size of the droplets of the emulsion gel prepared by using the shellac nanoparticle-cationic starch composite of this embodiment is 258 μm, the droplet particle size distribution is uniform, and the emulsion stability is high.
[0066] Comparative Example 1
[0067] A method for preparing an emulsion using individual shellac nanoparticles comprises the following steps:
[0068] 1 g of shellac was dissolved in 60 mL of anhydrous ethanol, and the anhydrous ethanol solution containing shellac was quickly injected into 140 mL of distilled water with a syringe to obtain a shellac nanoparticle solution. Subsequently, the solution was rotary evaporated to 100 mL at 40° C. and 100 rpm to obtain a shellac nanoparticle solution with a concentration of 1% (w / v).
[0069] Soybean oil was added to the shellac nanoparticle solution at a volume ratio of 3:7, and a high-speed shear homogenization process was performed using a homogenizer at a shear rate of 13000 r / min for 3 min to obtain an emulsion.
[0070] The test results of the particle size of the emulsion gel prepared in Comparative Example 1 show that the droplet particle size of the emulsion prepared by using the shellac nanoparticle emulsifier in this comparative example is 174 μm, the droplet particle size is too large, and the emulsion stability is poor.
[0071] Comparative Example 2
[0072] A method for preparing an emulsion using tapioca starch alone comprises the following steps:
[0073] 5g of cassava starch was dissolved in 500mL of isopropanol and stirred at room temperature for 15min. 25mL of 2M NaOH solution was added dropwise, stirred for 60min, 17mL of HAC solution was added, and the mixture was stirred in a 60℃ water bath for 5h. After the reaction, the pH was adjusted to 6.2 with 0.1M hydrochloric acid solution, 250mL of anhydrous ethanol was added, and the precipitate sample was obtained by suction filtration. The sample was rinsed with anhydrous ethanol for 3 to 5 times and then filtered, and placed in a 40℃ oven for drying to obtain HAC-modified cassava starch. 0.25g of HAC-modified cassava starch was dissolved in 25mL of water, placed in a 90℃ water bath, and reacted for 30min with 500rpm magnetic stirring to obtain a 1% (w / v) cassava solution.
[0074] Soybean oil was added to the cassava solution at a volume ratio of 3:7, and an emulsion was obtained by high-speed shear homogenization using a homogenizer at a shear rate of 13000 r / min for 3 min.
[0075] The particle size test results of the emulsion prepared in Comparative Example 2 show that the droplet particle size of the emulsion gel prepared by using the cassava starch emulsifier in this comparative example is 177 μm, and the emulsion stability is poor, which is manifested by the stratification phenomenon of the fresh emulsion.
[0076] The comparison of the emulsion states of Comparative Example 1, Comparative Example 2, Example 1 and Example 2 at different times is shown in Table 1
[0077] Table 1: Emulsion states at different times in Comparative Example 1, Comparative Example 2, Example 1 and Example 2
[0078]
[0079] Depend on Figure 1 As can be seen from Table 1, the emulsion gel prepared from the shellac nanoparticle-cationic starch composite in Example 1 has excellent performance, and shows significant advantages in emulsion stability and particle size control. The emulsion has a smaller droplet size and is evenly distributed, which greatly improves the stability of the emulsion or emulsion gel. Therefore, the emulsion gel that can reduce the emulsion droplet size, has a simple preparation process and significantly improves the storage stability is of great significance to the design of nutrient delivery carriers and the functionalization of active substances in food. The present invention uses shellac as a raw material and has the characteristics of biodegradability, biocompatibility, pH responsiveness, etc., which expands the application range of shellac. The shellac nanoparticles and cationic starch are compounded through hydrogen bonds and ionic bonds, which is a safe and non-toxic method for improving the stability of emulsions or emulsion gels.
[0080] The storage modulus (G'), loss modulus (G") and apparent viscosity test results of the emulsions in Comparative Example 1, Comparative Example 2 and Example 1 are as follows: Figure 2 and Figure 3 As shown:
[0081] Depend on Figure 2 It can be seen that the emulsion gel prepared from the shellac nanoparticle-cationic starch composite in Example 1 shows significantly enhanced storage modulus and loss modulus compared with the emulsions prepared from Comparative Examples 1 and 2. Figure 3 It can be seen that the viscosity of the emulsion prepared by Example 1 is higher than that of the emulsions prepared by Comparative Examples 1 and 2, so it can be judged that the gel strength of the emulsion prepared by the composite is greater than that of the emulsion prepared by the emulsifier alone. The compact gel structure enables it to efficiently deliver nutrients and improve the absorption efficiency of hydrophobic bioactive substances. Therefore, the composite emulsion gel can be used as a new nutrient delivery carrier and is widely used in the fields of nutrient delivery, drug controlled release, and bioactive substance stabilization, promoting the application of shellac in scientific research and food industry.
[0082] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0083] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the invention, and the scope of the invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing an emulsion gel using a shellac nanoparticle-cationic starch complex, characterized in that: The following steps are involved: S1. Material preparation: prepare shellac, starch, 3-chloro-2-hydroxypropyl-trimethylammonium chloride solution, distilled water and soybean oil, wherein the starch includes but is not limited to tapioca starch, corn starch and potato starch; S2. preparing a shellac nanoparticle solution A: dissolving shellac in anhydrous ethanol, and then quickly injecting the anhydrous ethanol solution containing shellac into distilled water with a syringe to obtain a shellac nanoparticle solution, and then performing rotary evaporation to obtain a shellac nanoparticle solution A; S3, preparing cationic starch solution B: dissolving starch in isopropanol, and stirring at room temperature, then adding sodium hydroxide solution dropwise, while continuing to stir, then adding 3-chloro-2-hydroxypropyl-trimethylammonium chloride solution and stirring in a water bath to react, after the reaction is completed, using an acid to adjust the pH value to 6.2, adding anhydrous ethanol and filtering to obtain a precipitated sample, then rinsing the sample several times and filtering again and finally drying to obtain cationic starch, dissolving the cationic starch in distilled water, heating in a water bath and magnetically stirring, and finally obtaining cationic starch solution B; S4, preparing a mixed solution C: adding the shellac nanoparticle solution A obtained in step S2 to the cationic starch solution B in step S3 to obtain a shellac nanoparticle-cationic starch mixed solution C; S5, preparing an emulsion gel: adding soybean oil to the mixed solution C obtained in step S4, and subjecting the mixed solution C with the soybean oil to high-speed shear homogenization treatment to obtain an emulsion gel.
2. The method for preparing an emulsion gel using a shellac nanoparticle-cationic starch complex according to claim 1, characterized in that: The temperature in the rotary evaporation of step S2 is 40° C. and the rotation speed is 100 r / min. The concentrations of the shellac nanoparticle solution A in step S2 and the cationic starch solution B in step S3 are both 0.5% to 1.0% (w / v).
3. The method for preparing an emulsion gel using shellac nanoparticle-cationic starch complex according to claim 1, characterized in that: In step S3, 3-chloro-2-hydroxypropyl-trimethylammonium chloride solution is added to carry out stirring reaction in a water bath, the water bath heating temperature is 70° C. to 90° C., the heating time is 10 to 40 minutes, and the acid agent in step S3 is 0.1M hydrochloric acid solution.
4. The method for preparing an emulsion gel using shellac nanoparticle-cationic starch complex according to claim 1, characterized in that: The stirring rate of the magnetic stirring in step S3 is 300-500 rpm. The steps of rinsing the sample multiple times, filtering again and finally drying in step S3 are as follows: rinsing the sample 3-5 times with anhydrous ethanol, filtering again and then drying in an oven.
5. The method for preparing emulsion gel using shellac nanoparticle-cationic starch complex according to claim 1, characterized in that: In step S5, the high-speed shearing rate of the homogenizer is 9000-15000 r / min for 2-4 min. In step S4, the volume ratio of the shellac nanoparticle solution A to the cationic starch solution B includes but is not limited to 5:1, 4:1, 2:1 and 1:
2.
6. The method for preparing emulsion gel using shellac nanoparticle-cationic starch complex according to claim 1, characterized in that: In step S5, the volume ratio of the mixed solution C to the soybean oil includes but is not limited to 4:1, 7:3, 3:2, 5:5, 2:3, 3:7 and 1:4.